2015
DOI: 10.1007/s13632-015-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

The Brass Nails of the Akko Tower Wreck (Israel): Archaeometallurgical Analyses

Abstract: The shipwreck designated as the Akko Tower Wreck was discovered inside Akko harbor, Israel, in 1966. It was surveyed in 1975 and 1981, and excavated in 2012-2013. Hull planks were connected to the frames by brass nails, some of which were in situ, emerging vertically from the planking, where frames had disappeared, and others were detached. The 105 nails that were retrieved were tentatively divided into two groups (A and B) according to their general shape and size. Nails sampled from each group were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(36 reference statements)
1
14
0
1
Order By: Relevance
“…During the study of the brass spikes retrieved from the shipwreck, an attempt was made to identify the probable origin of the ores using lead isotope analysis. It is suggested that the raw material for the production of the spikes derived from a common metal source, most probably British ores from Wales or Cornwall (Cohen et al ., : 202–3). The spikes could have been manufactured from raw material that was imported from Great Britain, or made in Great Britain and shipped ready to use to the shipyard where the ship was constructed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study of the brass spikes retrieved from the shipwreck, an attempt was made to identify the probable origin of the ores using lead isotope analysis. It is suggested that the raw material for the production of the spikes derived from a common metal source, most probably British ores from Wales or Cornwall (Cohen et al ., : 202–3). The spikes could have been manufactured from raw material that was imported from Great Britain, or made in Great Britain and shipped ready to use to the shipyard where the ship was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all spikes contained 0.5–1.1 wt% lead. Therefore, based on the zinc and lead concentrations, it is suggested that the brass spikes were most probably manufactured in the first half of the 19th century (Cohen et al ., : 199, 202).…”
Section: Datingmentioning
confidence: 97%
“…In the literature, brass-based metallic nails were studied in relationship with corrosion issues (mainly in shipwreck findings [29]). The history of brass refers to the deliberate addition of zinc to copper since the first millennium BC.…”
Section: Elementmentioning
confidence: 99%
“…Therefore, we cannot derive a strict chronological criterion to date the nail, though the low content presence of iron (up to 0.5%) and lead (less than 2%) suggests that nail 1 could have been produced in the 18th century [29]. Additionally, this nail, having a Cu/Zn ratio of 70/30, should have been produced before the use of the Muntz patent (concerning a brass metal having a Cu/Zn ratio equal to 60/40, patented in 1832 [29]).…”
Section: Elementmentioning
confidence: 99%
“…Metallographic examination of ancient metal artefacts retrieved from shipwrecks reveals their microstructure and correspondingly exposes information regarding their manufacturing processes [11][12][13][14][15][16][17][18][19]. Defining moments in the development of the metallographic scientific field were in 1751, when the geologists Widmanstätten and Schreibers etched various meteorites and exposed their crystalline patterns that could be viewed with a naked eye; and in 1808 when they revealed the well-known Widmanstätten structure by macro-etching [20,21].…”
Section: Metallographic Inspection Of Ancient Metal Artefacts Retrievmentioning
confidence: 99%